Off-Record Strategies In Spousal Conflict: Violation Of The Principle Of Cooperation And Its Implications - Ni Wayan Novi Wulandari; I Dewa Putu Wijana (Jurnal Ilmiah Global Education, 2026)
This study analyzes Off-Record Strategies in the speech acts of married couples during conflict, based on dialogue from the film "Noktah Merah Perkawinan." This qualitative study uses a pragmatic approach, focusing on Brown and Levinson's Politeness Strategy theory and Grice's Cooperative Principle. The results show that implicit directive speech acts are predominantly used by married couples to express criticism. These Off-Record strategies are realized through systematic violations of the Cooperative Principle, including Violations of Quality (Irony/Sarcasm and Rhetorical Questions), Violations of Quantity, Violations of Relevance, and Violations of Manner. The primary function of these principle violations is to launch harsh criticism and moral demands on the partner while avoiding responsibility for verbal aggression. Thus, Off-Record serves as a weapon that corners the partner's character and prolongs the conflict.